2015
DOI: 10.7150/thno.10853
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the In Vivo and In Vitro Effects of Photodynamic Therapy on Breast Cancer by Using a Sensitizer, Sinoporphyrin Sodium

Abstract: Photodynamic therapy (PDT) is an emerging theranostic modality for various cancers and diseases. Photosensitizers are critical components for PDT. Sinoporphyrin sodium, referred to as DVDMS, is a newly identified photosensitizer that was isolated from Photofrin. Here, we evaluated the effects of DVDMS-mediated PDT (DVDMS-PDT) on tumor cell proliferation and metastasis in the highly metastatic 4T1 cell line and a mouse xenograft model. DVDMS-PDT elicited a potent phototoxic effect in vitro, which was abolished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 50 publications
4
68
0
1
Order By: Relevance
“…The structure and property of sensitizer greatly affect the efficiency of PDT. Our previous studies have shown good photosensitivity of DVDMS against various cancers . We speculate that DVDMS mediated PDT (DVDMS‐PDT) would also produce significant potential in PACT.…”
Section: Discussionmentioning
confidence: 88%
“…The structure and property of sensitizer greatly affect the efficiency of PDT. Our previous studies have shown good photosensitivity of DVDMS against various cancers . We speculate that DVDMS mediated PDT (DVDMS‐PDT) would also produce significant potential in PACT.…”
Section: Discussionmentioning
confidence: 88%
“…The prolonged 980 nm excitation resulted in an increasedp hototoxicity effect measured by proliferation MTT assay commonly applied to evaluate cell sensitivity or cell death after photodynamic protocols [61,62] (Figure5d). The prolonged 980 nm excitation resulted in an increasedp hototoxicity effect measured by proliferation MTT assay commonly applied to evaluate cell sensitivity or cell death after photodynamic protocols [61,62] (Figure5d).…”
Section: Fret-based Interaction Between Ucnps and Vp Moleculesmentioning
confidence: 99%
“…On this ground, we herein report a multifunctional theranostic agent that integrates imaging and therapy functionalities into a single nano‐platform for highly efficient imaging‐guided SDT. Organic sinoporphyrin sodium (DVDMS) molecules were initially used as the sonosensitizer since they have been widely used in PDT and SDT for the therapy of many human tumours . Paramagnetic Mn centres were further anchored into DVDMS molecules (DVDMS‐Mn) by directly chelating manganese ion (Mn 2+ ) into DVDMS.…”
Section: Introductionmentioning
confidence: 99%
“…Organic sinoporphyrin sodium (DVDMS) molecules were initially used as the sonosensitizer since they have been widely used in PDT and SDT for the therapy of many human tumours. [28][29][30] Paramagnetic Mn centres were further anchored into DVDMS molecules (DVDMS-Mn) by directly chelating manganese ion (Mn 2+ ) into DVDMS. To improve the delivery efficiency, the multifunctional sonosensitizer DVDMS-Mn were further encapsulated into liposomes via a typical thin-film rehydration method to fabricate DVDMS-Mn-Liposomes (DVDMS-Mn-LPs).…”
Section: Introductionmentioning
confidence: 99%